Evaluasi Kinerja Pegawai Bagian Program Kemitraan dan Bina Lingkungan pada PT. Perkebunan Nusantara III (Persero) Medan - Abdul Kadir (Universitas Negeri Medan, 2018)
This study aims to determine the Employee Performance Evaluation of the Partnership and Community Development Program Section at PT. Perkebunan Nusantara III (Persero) Medan. Employee performance is the work that can be achieved by a person or group of people in an organization according to the authority and responsibility of each in order to realize the goals of the organization, which here will evaluate the performance of employees in the Partnership and Community Development Program at PT. Nusantara Nusantara III (Persero) Medan in 2016. Where many indicators can measure the performance of an employee. By looking at several indicators to determine performance success, namely productivity, service quality, responsiveness, responsibility and accountability, in this study using qualitative descriptive methods, the location of the study was conducted at the Office of the Partnership and Community Development Program at PT. Perkebunan Nusantara III (Persero) Medan, Data collection techniques are interviews, observation and documentation, it can be concluded that the Employee Performance Evaluation Section of the Partnership and Community Development Program at PT. Perkebunan Nusantara III (Persero) Medan is very good.